Occurrence of three-rooted permanent mandibular molar and its possible link with archaic human - an overview (Bulletin of the International Association for Paleodontology, 2021)
Occurrence of 3-rooted mandibular molar varies from one geographical and ethnic group to other. Its prevalence is very high in Asian and Asian-derived populations, particularly Aleuts and Eskimos. The recently revealed individual from Xiahe, China - recognised as Denisovan shows a 3-rooted lower permanent molar, giving a direct morphological link between archaic and recent Asian Homo sapiens population. This area of study is useful in archaeology, palaeontology, physical anthropology and forensic pathology/ dentistry. Its application is also important in clinical dentistry.